Improved hurricane wind speed algorithm for the seawinds satellite scatterometer - Kasparis, Takis; Adams, Ian S.; Jones, Wilma L. (My University, 2002)
Satellite microwave scatterometer wind retrievals, given in the standard product (e.g., QuikSCAT L2B), badly underestimate the peak wind speed in tropical cyclones. One important reason is that the effects of precipitation on the normalized radar cross section sigma-0 are neglected in the processing algorithms. This paper presents results of a first attempt to provide sigma-0 corrections, which account for the atmospheric attenuation of the rain. Atmospheric transmissivity is derived from the QuikSCAT Radiometer (QRAD) excess brightness temperatures taken simultaneously with sigma-0 measurements. When applied, retrieved wind speeds show improved agreement with numerical hurricane models (PSU/NCAR MM5) where there is moderate to high rainfall.
Keywords: Atmospheric radiation; Microwaves; Algorithms; Electromagnetic waves; Hurricanes